PENINGKATAN HASIL BELAJAR SISWA MELALUI MODEL QUANTUM TEACHING BERBANTUAN MEDIA APLIKASI EDMODO PADA SISWA SEKOLAH DASAR - Cahyo Tris Diantoro; Erik Aditia Ismaya; Eko Widianto (WASIS : Jurnal Ilmiah Pendidikan, 2020)
This study aims to describe the improvement of teacher teaching skills with the application of the Quantum Teaching model assisted by edmodo application media and describe the improvement of student learning outcomes in social studies content and Indonesian language class IV SDN Doropayung 01.The research method used is classroom action research. This research was conducted in two cycles, each of which consisted of planning, action, observation and reflection. The subject of the research is the fourth grade students of SDN Doropayung 01 with a total of 20 students. The data source of this research is the teacher, students. Data collection techniques include interview, observation, test and documentation techniques. Data validity uses expert judgment techniques and data analysis used is qualitative and quantitative data analysis.The results showed that the Quantum Teaching model assisted by edmodo application media can improve teacher teaching skills, student learning outcomes aspects of knowledge and skills. Teachers' teaching skills showed an increase in which in the first cycle obtained a score of 80 and the percentage of success of 80% with a good category, then in the second cycle scored 86 and the percentage of success by 86% with very good criteria. Student learning outcomes have increased aspects of knowledge, the social studies content of the first cycle 70% and cycle II to 83%. Furthermore, on the Indonesian content the percentage of classical completeness of students in the first cycle was 70%, then increased in the second cycle to 77%. Student learning outcomes in the aspect of skills also increased, in the first cycle of 78%, then in the second cycle increased significantly to 83% with a very good category.